DIRECTIVE ILLOCUTIONARY ACTS FOUND IN “THE GUILTY” MOVIE 2021 - Arini, Ni Kadek Ayu Arini; Komang Dian Puspita Candra (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
The article embarks on an in-depth exploration of the diverse directive illocutionary acts depicted in the 2021 film "The Guilty." Its primary aim lies in meticulously analyzing and categorizing the instances of directive illocutionary acts portrayed by the characters throughout the movie, drawing data from their dialogues and interactions. Guided by the theoretical framework of Searle and Vanderveken, the research employs a qualitative descriptive methodology to dissect the nuances of each directive illocutionary act, revealing four distinct types prevalent in the film: commands, requests, advice, and asks. With a total of 44 instances identified, including 25 commands, 12 requests, 4 instances of advice, and 3 asks, this thorough examination not only sheds light on the prevalence of directive illocutionary acts within "The Guilty" but also underscores their significance in shaping interpersonal dynamics and propelling the narrative forward.